The ultrastructural nature of human oocytes' cytoplasmic abnormalities and the role of cytoskeleton dysfunction - Tatíčková, Martina; Trebichalská, Zuzana; Kyjovská, Drahomíra; Otevřel, Pavel; Kloudová, Soňa; Holubcová, Zuzana (F&S science, 2023)
OBJECTIVE: To investigate the structural bases of human oocytes' cytoplasmic abnormalities and the causative mechanism of their emergence. Knowledge of an abnormal oocyte's intracellular organization is vital to establishing reliable criteria for clinical evaluation of oocyte morphology. DESIGN: Laboratory-based study on experimental material provided by a private assisted reproduction clinic. SETTING: University laboratory and imaging center. PATIENTS: A total of 105 women undergoing hormonal stimulation for in vitro fertilization (IVF) donated their spare oocytes for this study. INTERVENTIONS: Transmission electron microscopy (TEM) was used to analyze the fine morphology of 22 dysmorphic IVF oocytes exhibiting different types of cytoplasmic irregularities, namely, refractile bodies; centrally located cytoplasmic granularity (CLCG); smooth endoplasmic reticulum (SER) disc; and vacuoles. A total of 133 immature oocytes were exposed to cytoskeleton-targeting compounds or matured in control conditions, and their morphology was examined using fluorescent and electron microscopy. MAIN OUTCOME MEASURES: The ultrastructural morphology of dysmorphic oocytes was analyzed. Drug-treated oocytes had their maturation efficiency, chromosome-microtubule configurations, and fine intracellular morphology examined. RESULTS: TEM revealed ultrastructural characteristics of common oocyte aberrations and indicated that excessive organelle clustering was the underlying cause of 2 of the studied morphotypes. Inhibition experiments showed that disruption of actin, not microtubules, allows for inordinate aggregation of subcellular structures, resembling the ultrastructural pattern seen in morphologically abnormal oocytes retrieved in IVF cycles. These results imply that actin serves as a regulator of organelle distribution during human oocyte maturation. CONCLUSION: The ultrastructural analogy between dysmorphic oocytes and oocytes, in which actin network integrity was perturbed, suggests that dysfunction of the actin cytoskeleton might be implicated in generating common cytoplasmic aberrations. Knowledge of human oocytes' inner workings and the origin of morphological abnormalities is a step forward to a more objective oocyte quality assessment in IVF practice.
Keywords: Oocytes; Cytoskeleton; dysmorphism; Microtubules; Cytoplasm; oocyte abnormalities; lidé; Female; electron microscopy; human oocyte; mikrotubuly; aktiny; oocyty; Actins; cytoplazma; ženské pohlaví; cytoskelet; Humans